Death and redemption : the Gulag and the shaping of Soviet society - Barnes, Steven Anthony (Princeton University Press, 2011)
Death and Redemption offers a fundamental reinterpretation of the role of the Gulag--the Soviet Union's vast system of forced-labor camps, internal exile, and prisons--in Soviet society. Soviet authorities undoubtedly had the means to exterminate all the prisoners who passed through the Gulag, but unlike the Nazis they did not conceive of their concentration camps as instruments of genocide. In this provocative book, Steven Barnes argues that the Gulag must be understood primarily as a penal institution where prisoners were given one final chance to reintegrate into Soviet society.